Hyperpaysages : à l’affût de territoires réticulaires et mentaux - Lévesque, Luc (CV Photo, 2001)
Although, by working to push the limits of the gaze, photography indirectly contributes to stimulating new paths for the garden, the elusive complexity of the garden reciprocally defies capture by the photograph. Landscape is a key concept for photography and for gardens. Referring to the hypertextuality made possible by new modes of computer communication, the notion of hyperlandscape suggests a gaze that examines the transience and apparent insignificance of things to extract new paths for creativity. When we plunge into the ubiquitous media, we are confronted with the growing disaggregation of levels of the reality; as with the hyperlink, something insignificant can open up to a universe.